Differential diagnosis of pathomorphological changes in the lungs of pregnant children in certain components of the metabolic syndrome of the mother. - Rudiak, O. M. (Морфологія / Morphologia / Morfologìâ, 2019)
Backgroud. The metabolic syndrome of the mother and the effect of its components on the fetal development is the focus of medical science and health care. Also known that it is the close relationship between functional immaturity of the organs and tissues of the fetus and comorbidities of the mother, especially type 2 diabetes, hypertension, obesity and dyslipidemia. Objective is to carry out differential diagnosis of pathomorphological changes in the lungs of premature infants in the study groups. Methods. The studies were performed on the section material of the lungs of premature infants of 29-33 weeks of gestation (120 cases), which were divided into three groups depending on the components of the metabolic syndrome of the mother. Results. Moderate swelling of the mucous membrane, areas of blood filling, venous plethora, mucous membrane in segmental bronchial tubes of children of group I are observed. Segmental bronchi of children of group II corrugated and swollen, hyperplastic growths of the ciliated prismatic epithelium are observed. In group III of the study, the mucous membrane of the segmental bronchi is represented by a multilayered ciliated cylindrical epithelium; Morphometric parameters of the epithelial cells of the respiratory parts of the lungs of premature infants in the three study groups indicate a lag in their differentiation processes, which delay the structural and functional development of lung tissue. Conclusion. Differential diagnostics of pathomorphological changes in the lungs of premature infants in the study groups revealed immaturity of the lung tissue, which corresponds to the specified gestation periods, and their morphological changes are related to the influence of maternal factors, such as hypertension, diabetes mellitus, diabetes mellitus.